Glufosinate Ammonium Residues in Different Soils and Water of Oil Palm Ecosystem - Mohd. Jani, Siti Jariani (2010)
In Malaysia, the herbicide glufosinate ammonium (GLUF) is widely used in oil palm plantations mainly for the control of weeds and grasses, thus making it easier for collection of palm oil fruits and to ensure safety of workers against wild animals. Currently, lifecycle assessment of environmental impacts is a requirement particularly for products that are exported such as palm oil and there is lack of documented data on the residues of GLUF in the oil palm ecosystem to support the lifecycle assessment Therefore, it is important for the industry to have a relevant data to prove that there is no environmental impact on the herbicide practices especially for oil palm which is exported to countries that requires high environmental safety standards. Hence, the main objective of this study is to investigate the behavior and possible residues of GLUF in soil and water of oil palm ecosystem through three specific objectives: 1) To determine the adsorption and desorption of GLUF in different soils under oil palm cultivation, 2) to determine the degradation of GLUF in different soils under oil palm cultivation and 3) to determine the residues of GLUF in soil and water of oil palm plantation. In order to achieve the first objective, adsorption and desorption study were conducted on four mineral soils, Inceptisol (Selangor), Oxisol (Munchong) and Ultisols (Serdang and Rengam) series and a peat soil (Histosol) collected under oil palm cultivation from 0-15 cm and 15-30 cm depths using batch equilibrium technique. The concentrations of GLUF used were 0, 0.25, 0.5, 1, 1.5, 3, 5 and 10 μg/mL. The adsorption and desorption isotherms were fitted to the linear and Freundlich equations. Adsorption of GLUF was in the following increasing order: Selangor > Rengam> Munchong> peat > Serdang. The results indicated that the adsorption of GLUF was positively correlated only with clay content. The high sorption of the Selangor series soil could be explained by the high clay content in this soil series compared to the other soil series. In contrast, the order of GLUF desorption was in the following order: Serdang> peat> Munchong> Rengam> Selangor. Results indicate that adsorption of GLUF was mainly on the clay fraction of the soil and the binding strength of adsorbed GLUF was high as indicated by low amount of GLUF desorbed from the soils. The second objective was achieved through a degradation study in the laboratory using incubation technique. The effects of microbial activity on GLUF were studied in three soil series (Selangor, Serdang and peat) collected at 0-15 cm depth. The soils were either sterilized or non-sterilized and both were treated with either a recommended field dose (3.333 L/ha) of GLUF or double recommended field dose. Each soil treatment was done in triplicates. Samples were analyzed at 0, 2, 4, 8, 12, 16, 24, 35, 42 and 60 days after treatment. Sterile soil showed no significant changes in all 3 types of soil compared to the non-sterile soil. This can be explained by the lack or no microbial activity in the sterile soil. The results indicate that microbial activity played an important role in the degradation of GLUF. In non-sterile soil for both dosage of GLUF application, the shortest half-life was observed in peat soil with 4.61 and 15.5 days for the recommended and double recommended dose, respectively. Selangor Series Soil (clay) exhibited the longest half-life of 10.02 and 37.45 days in the recommended and double recommendedfield dose, respectively. A field experiment was conducted to achieve the third objective. The type of soil at the site was clay soil. The study plots were arranged in Completely Randomized Design (CRD) and the study was conducted at two different seasons, the rainy and dry season. In this study, GLUF was applied at a recommended dose and double recommended dose. During the rainy season, the GLUF residues were still detected in the soil at day 3 after application of the recommended field dose and day 7 for application of double recommended field dose. There were no detected residues in the water collected from PVC tube installed in the field and sub stream for both doses. Residues of GLUF remained longer in the soil during the dry season. The residues were still detected at day 21 and 42 for the recommended and double recommended field dose, respectively. No water sample was collected during the dry season because the sub stream and PVC tube were all dried up. This is due to the low rainfall at that time of the season. From all the results obtained, it can be concluded that GLUF is safe to be used in oil palm plantation as it has a very short half-life and low potential of GLUF to be transported or leached to the groundwater if used as recommended. However, the impact of the herbicide on the environment depends on more factors than these, for examples, its impact to soil microorganism, non-target organism and aquatic environment. The use of this herbicide in agriculture environment might lead to their occurrence in nonagricultural environment. Herbicides that have a high leaching potential can result in the contamination of ground water supplies.